The Influence of Education, Training, and Competency on the Performance of PT. XYZ - Wulandari, Anggita; Sungkono, Sungkono (Integrasi Sains Media, 2023)
One way to improve the quality of PT. XYZ is implemented, planned, and systematically through education, training, and existing competencies. In other words, the importance of education and training in the organization is the improvement of employee performance which includes knowledge and skills that support, as well as the formation of the attitude of each employee as desired by the organization. This study uses an explanatory type of research with a quantitative approach. The independent variables used in this study were education and training (X1) with formal and non-formal education indicators, competence (X2) with indicators of leadership training, functional training, and technical training. The dependent variables in this study are performance with indicators of quantity, quality, and attitude/reliability.